2021
DOI: 10.24085/jsaa.v9i2.3699
|View full text |Cite
|
Sign up to set email alerts
|

Advisors’ Perceptions of the Value of Advising Students During the COVID-19 Pandemic: A Case Study at a South African University

Abstract: Traditional advising responsibilities are shifting to include a holistic, learning-based and developmental approach that favours advising of the entire university experience. A dearth of systematic empirical evidence exists on advisors’ perceptions of the value of advising students during the COVID-19 pandemic in the South African context. The purpose of this study is to elucidate advisors’ perceptions of the complexity and challenges inherent in their responsibilities during the pandemic. This case study draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The consequences of forgoing NSFAS or other financial aid monies in this way can be catastrophic and must not be discounted when considering the complex social realities students bring to the advising engagement or the institution more broadly. Importantly, these data must be utilised to develop and implement responsive strategies for enabling student success and for improving the integration of academic advising with all other components of South African HEIs (Moosa, 2021), to ensure that students (especially those most affected by the complex realities of the South African higher education sector) reap the benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequences of forgoing NSFAS or other financial aid monies in this way can be catastrophic and must not be discounted when considering the complex social realities students bring to the advising engagement or the institution more broadly. Importantly, these data must be utilised to develop and implement responsive strategies for enabling student success and for improving the integration of academic advising with all other components of South African HEIs (Moosa, 2021), to ensure that students (especially those most affected by the complex realities of the South African higher education sector) reap the benefits.…”
Section: Discussionmentioning
confidence: 99%
“…As the South African higher education sector shifts beyond emergency modes of instruction towards a post-pandemic reality, the conditions for change may be in place: the inequities entrenched in the sector are known and cannot easily be ignored (Czerniewicz et al, 2020); academic advising has emerged as a previously undervalued practice that can bridge gaps between the student, the institution, and the lecturer (De Klerk, 2022;Moosa, 2021); and calls for intentional shifts towards student-focused pedagogies and holistic student support within the South African higher education sector are on the rise. Now is the time for the South African higher education sector and its institutions to draw on the wisdom of these insights beyond paying lip-service to student challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the COVID-19 pandemic has posed challenges, particularly in a virtual context, hindering advisors from effectively serving students (Yoder, 2021). Moosa's (2021) case study at a South African university emphasized how advising during the pandemic differs greatly from the prepandemic era. The results of their study also indicated dissemination of information as one of the major obstacles in their advising career during the pandemic.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Students' needs are identified during the advising process since advising typically involves guiding students through their university career with issues such as finances, curriculum planning, scheduling classes, understanding degree requirements, referral to resources and setting personal and career goals. Advisors' responsibilities are thus broad and include the entire university experience (Moosa, 2021). Advisors' ability to adapt to address students' changing needs is dependent on the repertoire of appropriate theories that they have to draw on to inform their knowledge base.…”
Section: Introductionmentioning
confidence: 99%